DEFAULT IN OF LEGAL AID COLLABORATION AGREEMENT BETWEEN ADVOCATES AND REGIONAL GOVERNMENTS OF CENTRAL BENGKULU REGENCY - Febricka Riezky Ramadhanti; Ganefi Ganefi; Candra Irawan (Universitas Bengkulu, 2021)
This study aimed to determine and analyze the implementation of the cooperation contract between the Regional Government of Central Bengkulu Regency and advocates in the field of providing legal aid and to find out and analyze the settlement in the event of a dispute in the implementation of a cooperation contract between the Regional Government of Bengkulu Tengah Regency and an advocates in the field of providing legal aid. This research was an empirical research and the data analysis used was qualitative with deductive-inductive thinking method. The results showed that the cooperation contract between the Regional Government of Bengkulu Tengah Regency and advocates in the field of providing legal assistance was carried out through a written agreement. The legal basis for the cooperation contract was based on Article 9 letter a and b of Law Number 16 of 2011 concerning Legal Aid, specifically stipulated by the Decree of the Regent of Central Bengkulu Number 3 of 2013 concerning the Stipulation of Advocates/Lawyers in the Context of Resolving Legal Problems for Civil Servants/Apparatus in the Regional Government of Central Bengkulu Regency in 2013 and all costs in the implementation of the cooperation contract for the provision of legal assistance were borne by the Regional Government of Central Bengkulu Regency through Number DPA 1.20 (1.20.03) .20.09.5.2. Whereas the obstacles in implementing the cooperation contract between the Regional Government of Central Bengkulu Regency and advocates in the field of providing legal assistance included the payment of honorariums to lawyers who were often late or paid once every three months, as a result lawyers could not carry out their duties and functions properly. The settlement of these obstacles by both parties agreed to do non-litigation, which was negotiations, so that the cooperation agreement would not be broken.